Preparation method for expanding interlayer spacing of two-dimensional lamellar material through self-generation of carbon dioxide by cooperation of phytic acid and urea
By inserting phytic acid and urea into the two-dimensional sheet material and generating carbon dioxide, the problem of insufficient layer spacing expansion and insufficient flame retardant effect of the two-dimensional sheet material is solved, and better layer spacing expansion and flame retardant performance are achieved.
Patent Information
- Application Number
- CN202411683427.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-22
- Publication Date
- 2025-03-14
AI Technical Summary
The gap between the existing two-dimensional sheet materials is not significantly expanded, and the flame retardant effect in the matrix material needs to be improved.
The layer spacing of the two-dimensional lamella material is expanded by inserting phytic acid and urea between layers of the two-dimensional lamella material and reacting it at a certain temperature to generate carbon dioxide.
The layer spacing of the two-dimensional sheet material is effectively expanded, and its flame retardant performance in the matrix material is improved. The method is environmentally friendly and harmless, easy to operate and low energy consumption.
Smart Images

Figure CN119612592A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of enlarging the interlayer spacing of two-dimensional sheet materials, and more specifically, relates to a preparation method for enlarging the interlayer spacing of two-dimensional sheet materials by using phytic acid to cooperate with urea to self-generate carbon dioxide. Background Art
[0002] Two-dimensional sheet materials are substances that have obvious dimensions only on a two-dimensional scale. This is a general term for a large class of materials. The earliest discovered two-dimensional sheet material was a single-layer graphene sheet isolated by the University of Manchester in 2004. With the advancement of science, the two-dimensional sheet materials discovered so far include montmorillonite, MoS 2 , black phosphorus, MXene, etc. Due to its unique two-dimensional structure, two-dimensional sheet materials can limit the movement of electrons only on a two-dimensional plane, so they are widely used in a series of electrical devices such as optoelectronic devices and thermoelectric devices. In addition, two-dimensional sheet materials have also been proven to have significant flame retardant effects in the field of flame retardancy. The two-dimensional sheet material is added to the matrix as a filler for flame retardancy. It utilizes the good stability of the two-dimensional sheet material at high temperatures and can serve as a good physical barrier to hinder heat transfer. However, the flame retardant effect of a single two-dimensional sheet material is not very good. By using two-dimensional sheet materials and other flame retardants in combination, the substrate can exhibit excellent flame retardant properties and mechanical properties.
[0003] Two-dimensional sheet materials often need to expand the interlayer spacing of two-dimensional sheet materials during use. The method of expanding the interlayer spacing of two-dimensional sheet materials is usually to use small molecules, metal ions and other substances to intercalate into the interlayer of two-dimensional sheet materials, so as to achieve the purpose of expanding the interlayer spacing of two-dimensional sheet materials. In the preparation method of a flame retardant additive in CN105733316B, the transition metal ions in the inorganic salt are first exchanged with the cations between the montmorillonite layers, effectively opening the interlayer spacing of the montmorillonite, and then adding an anion modifier organic acid salt, through the positive attraction of the cations between the montmorillonite layers and the hydrophobic effect of the long-chain alkyl, the anion modifier organic acid salt is successfully made to enter the interlayer of the montmorillonite, thereby further effectively opening the interlayer spacing of the montmorillonite, and improving the thermal stability and flame retardant properties of the polymer. However, the expansion of the interlayer spacing depends on the intercalation of the organic acid salt and the orientation of the interlayer to open the sheet, so the effect of expanding the interlayer spacing of the two-dimensional sheet material by the intercalation method is not obvious.
[0004] Phytic acid is a natural organophosphorus compound, which is regarded as a natural flame retardant and is widely used in various substrates to promote the carbonization of substrates. Urea can decompose to produce ammonia and carbon dioxide at high temperature, but urea itself does not have a flame retardant effect, so it needs to be used in combination with other flame retardants to achieve a flame retardant effect. In the preparation method of a phytic acid-modified magnesium aluminum hydrotalcite / montmorillonite nanomaterial in CN202210353637.3, montmorillonite is firstly ultrasonically stripped, and then the magnesium aluminum hydrotalcite is prepared in the montmorillonite solution by "urea decomposition-uniform coprecipitation method" to obtain MgAlLDH / MMT composite material, and finally phytic acid is used to further modify magnesium aluminum hydrotalcite / montmorillonite. This patent uses the synthesis of hydrotalcite between the layers of montmorillonite to achieve the effect of stripping montmorillonite. Urea is a component of synthetic hydrotalcite, which has been consumed in the process of synthesizing hydrotalcite. Simple ultrasonic treatment cannot strip montmorillonite into nanosheets. In addition, phytic acid only performs surface grafting modification on magnesium aluminum hydrotalcite / montmorillonite nanomaterials, and does not enter the interlayers thereof. It mainly uses hydrogen bonds and electrostatic forces to adsorb on the surface of magnesium aluminum hydrotalcite / montmorillonite nanoparticles. Therefore, the phytic acid in this patent does not synergistically enhance the interlayer spacing of the two-dimensional sheet material with urea to peel into sheets, nor does it synergistically enhance the flame retardant properties. Summary of the invention
[0005] In order to overcome the problems that the interlayer spacing of existing two-dimensional sheet materials is not significantly enlarged and the flame retardant effect needs to be improved when applied in base materials, the present invention provides a preparation method for enlarging the interlayer spacing of two-dimensional sheet materials by using phytic acid and urea to self-generate carbon dioxide.
[0006] The present invention is achieved through the following technical solutions:
[0007] A method for preparing a two-dimensional sheet material by using phytic acid to cooperate with urea to self-generate carbon dioxide to expand the interlayer spacing, the preparation steps comprising:
[0008] S1. dispersing the two-dimensional sheet material in deionized water to obtain a two-dimensional sheet material dispersion;
[0009] S2. adding phytic acid and urea to the dispersion of the two-dimensional sheet material, and inserting the phytic acid and urea into the interlamellar space of the two-dimensional sheet material through cation exchange or thermal motion of molecules;
[0010] S3. heating the solution of the intercalated two-dimensional sheet material so that the phytic acid between the layers reacts with urea to generate carbon dioxide;
[0011] S4. After the interlayer reaction of phytic acid and urea, an exfoliated nano two-dimensional sheet material is obtained.
[0012] Furthermore, the two-dimensional sheet material includes sodium montmorillonite, calcium montmorillonite, black phosphorus, Ti 4 N3 -MXene、Ti 3 C 2 T X -MXene、Ti 2 C-MXene、Nb 2 One or more of C-MXene, multilayer graphene, mica, diatomaceous earth, hexagonal boron nitride, molybdenum disulfide, mica, diatomaceous earth, hexagonal boron nitride, and molybdenum disulfide.
[0013] Furthermore, the dispersion described in S1 is carried out by ultrasonic dispersion, the ultrasonic time is 24 to 60 hours, and the ultrasonic frequency is 20 to 45 Hz.
[0014] Furthermore, the mass ratio of the two-dimensional sheet material to deionized water is 1:100-200.
[0015] Furthermore, the temperature of the cation exchange or the thermal motion of the molecules in S2 is 40 to 60°C, and the reaction time is 2 to 6 hours.
[0016] Furthermore, the molar ratio of phytic acid to urea is 1:5-12.
[0017] Furthermore, the mass ratio of the total mass of the phytic acid and urea to the two-dimensional sheet material is 12 to 28:1.
[0018] Furthermore, the reaction temperature in S3 is 80-100°C, and the reaction time is 2-7h.
[0019] Furthermore, the drying temperature in S4 is 40-65°C, and the reaction time is 6-10 hours.
[0020] Furthermore, the two-dimensional sheet material prepared by the preparation method of using phytic acid to cooperate with urea to self-generate carbon dioxide to expand the interlayer spacing of the two-dimensional sheet material is used in flame retardant materials.
[0021] Compared with the prior art, the beneficial effects are:
[0022] The method of the present invention utilizes the characteristics that phytic acid and urea can react at a certain temperature to form ammonium phytate and carbon dioxide. Urea and phytic acid are first inserted into the interlayer of the two-dimensional sheet through cation exchange or thermal motion of molecules, and then the carbon dioxide generated by the reaction of phytic acid and urea between the interlayers of the two-dimensional sheet material is used to further expand the interlayer spacing of the two-dimensional sheet material. The present invention also uses the phosphorus-nitrogen synergistic mechanism to fix the carbon dioxide when the carbon dioxide is generated between the layers by compounding phytic acid and urea, and can use the carbon dioxide between the montmorillonite layers to reduce the concentration of oxygen during the combustion process, so as to achieve an effective flame retardant effect.
[0023] Compared with the traditional method of using intercalants to expand the interlayer spacing, using carbon dioxide to generate and expand the interlayer spacing is environmentally friendly, mild, and does not require organic solvents, avoiding the environmental pollution and solvent residue problems in traditional methods. At the same time, by adjusting the temperature and reaction time, the content of carbon dioxide generated can be controlled, and the interlayer spacing can be precisely controlled, providing better customizability. In addition, this method is easy to operate, has low energy consumption, and has a better effect of expanding the interlayer spacing. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] Figure 1 is the XRD diagram of the interlayer spacing of the calcium-based montmorillonite prepared in Example 2, after the original, intercalation and exfoliation;
[0025] Figure 2 is a transmission electron microscope image of the exfoliated nano sodium-based montmorillonite prepared in Example 1;
[0026] Figure 3 This is a scanning electron microscope image of the exfoliated nanographene prepared in Example 5. DETAILED DESCRIPTION
[0027] The following is further explained and illustrated in conjunction with the examples, but the specific examples do not limit the present invention in any form. If not specifically stated, the methods and equipment used in the examples are conventional methods and equipment in the art, and the raw materials used are all conventional commercially available raw materials.
[0028] Example 1
[0029] This embodiment provides a preparation method and application of phytic acid cooperating with urea to self-generate carbon dioxide to expand the interlayer spacing of a two-dimensional sheet material, and the preparation steps include:
[0030] S1. Take 1 g of sodium-montmorillonite and disperse it in 100 g of deionized water. Ultrasonic treatment was performed for 24 h at an ultrasonic frequency of 45 Hz to obtain a sodium-montmorillonite dispersion (Na-MMT).
[0031] S2. Take 0.02 mol of phytic acid and 0.12 mol of urea, add them to the Na-MMT aqueous solution, the mass ratio of the total mass of phytic acid and urea to Na-MMT is 20:1, stir at 40°C for 2 hours to carry out cation exchange, so that the phytic acid and urea are intercalated into the interlayer of Na-MMT, and a montmorillonite solution intercalated with phytic acid and urea is obtained.
[0032] S3. Heat the intercalated montmorillonite solution to 80°C in an oil bath and stir for 2 hours, so that the intercalated phytic acid and urea react between the montmorillonite layers to produce carbon dioxide.
[0033] S4. Place the reacted sodium montmorillonite product into a drying oven and dry it at 40°C for 6 hours to prepare an exfoliated nano two-dimensional sheet material in which phytic acid cooperates with urea to self-generate carbon dioxide to expand the interlayer spacing of the two-dimensional sheet material.
[0034] Example 2
[0035] This embodiment provides a preparation method and application of phytic acid cooperating with urea to self-generate carbon dioxide to expand the interlayer spacing of a two-dimensional sheet material, and the preparation steps include:
[0036] S1. Take 2 g of calcium-montmorillonite and disperse it in 200 g of deionized water. Ultrasonic treatment was performed for 36 h at an ultrasonic frequency of 35 Hz to obtain a calcium-montmorillonite dispersion (Ca-MMT).
[0037] S2. Take 0.04 mol of phytic acid and 0.35 mol of urea, add them to the Ca-MMT aqueous solution, the mass ratio of the total mass of phytic acid and urea to Ca-MMT is 24:1, stir at 45°C for 3 hours to carry out cation exchange, so that the phytic acid and urea are intercalated into the interlayer of Ca-MMT, and a montmorillonite solution intercalated with phytic acid and urea is obtained.
[0038] S3. Heat the intercalated montmorillonite solution to 85°C in an oil bath and stir for 4 hours, so that the intercalated phytic acid and urea react between the montmorillonite layers to produce carbon dioxide.
[0039] S4. Place the reacted sodium montmorillonite product into a drying oven and dry it at 50°C for 7 hours to prepare an exfoliated nano two-dimensional sheet material in which phytic acid cooperates with urea to self-generate carbon dioxide to expand the interlayer spacing of the two-dimensional sheet material.
[0040] Example 3
[0041] This embodiment provides a preparation method and application of phytic acid cooperating with urea to self-generate carbon dioxide to expand the interlayer spacing of a two-dimensional sheet material, and the preparation steps include:
[0042] S1. Take 0.1 g of black phosphorus and disperse it in 20 g of deionized water, and treat it with ultrasound for 36 hours at a frequency of 20 Hz to obtain a black phosphorus dispersion.
[0043] S2. Take 0.002 mol of phytic acid and 0.01 mol of urea, add them to the black phosphorus dispersion, the mass ratio of the total mass of phytic acid and urea to black phosphorus is 19:1, stir at 50°C for 4 hours, so that the phytic acid and urea are intercalated into the interlayer of black phosphorus, and obtain a black phosphorus solution intercalated with phytic acid and urea.
[0044] S3. Heat the intercalated black phosphorus solution to 90°C in an oil bath and stir the reaction for 5 hours, so that the intercalated phytic acid and urea react between the layers of black phosphorus to produce carbon dioxide between the layers of black phosphorus.
[0045] S4. The finished black phosphorus product that has been reacted is placed in a drying oven and dried at 55°C for 8 hours to prepare an exfoliated nano two-dimensional sheet material in which phytic acid cooperates with urea to self-generate carbon dioxide to expand the interlayer spacing of the two-dimensional sheet material.
[0046] Example 4
[0047] This embodiment provides a preparation method and application of phytic acid cooperating with urea to self-generate carbon dioxide to expand the interlayer spacing of a two-dimensional sheet material, and the preparation steps include:
[0048] S1. Take 1g of multilayer Ti 4 N 3 -MXene was dispersed in 100 g of deionized water and ultrasonically treated for 48 h at a frequency of 30 Hz to obtain Ti 4 N 3 -MXene dispersion.
[0049] S2. Take 0.01 mol of phytic acid and 0.09 mol of urea and add them to Ti 4 N 3 -MXene dispersion, the total mass of phytic acid and urea and Ti 4 N 3 The mass ratio of Ti4N3-MXene was 12:1, and the mixture was stirred at 55 °C for 5 h to allow phytic acid and urea to be intercalated into the interlayer of Ti4N3-MXene to obtain Ti4N3-MXene intercalated with phytic acid and urea. 4 N 3 -MXene solution.
[0050] S3. The already intercalated Ti 4 N 3 -MXene solution, heated in an oil bath at 95 °C, stirred and reacted for 6 h, so that the intercalated phytic acid and urea were 4 N 3 -MXene layers react to form Ti 4 N 3 - Carbon dioxide is produced between the layers of MXene.
[0051] S4. The already reacted Ti 4 N 3 The -MXene finished product was placed in a drying oven and dried at 60°C for 9 hours to prepare an exfoliated nano two-dimensional sheet material in which phytic acid synergizes with urea to self-generate carbon dioxide to expand the interlayer spacing of the two-dimensional sheet material.
[0052] Example 5
[0053] This embodiment provides a preparation method and application of phytic acid cooperating with urea to self-generate carbon dioxide to expand the interlayer spacing of a two-dimensional sheet material, and the preparation steps include:
[0054] S1. 2 g of multilayer graphene was dispersed in 300 g of deionized water and ultrasonically treated for 60 h at an ultrasonic frequency of 40 Hz to obtain a multilayer graphene dispersion.
[0055] S2. Take 0.04 mol of phytic acid and 0.48 mol of urea, add them to the multilayer graphene dispersion, the mass ratio of the total mass of phytic acid and urea to the multilayer graphene T is 28:1, stir at 60°C for 6h, so that the phytic acid and urea are intercalated into the interlayers of the multilayer graphene, and obtain a multilayer graphene solution intercalated with phytic acid and urea.
[0056] S3. The intercalated multilayer graphene solution is heated in an oil bath at 100° C. and stirred for reaction for 7 hours, so that the intercalated phytic acid and urea react between the layers of the multilayer graphene to generate carbon dioxide between the layers of the multilayer graphene.
[0057] S4. The multilayer graphene product that has been reacted is placed in a drying oven and dried at 65°C for 10 hours to prepare an exfoliated nano two-dimensional sheet material in which phytic acid cooperates with urea to self-generate carbon dioxide to expand the interlayer spacing of the two-dimensional sheet material.
[0058] In the above embodiment, the two-dimensional sheet material used can also be Ti 3 C 2 T X -MXene、Ti 2 C-MXene、Nb 2 C-MXene, mica, diatomaceous earth, hexagonal boron nitride, molybdenum disulfide, mica, diatomaceous earth, hexagonal boron nitride, molybdenum disulfide.
[0059] The phytic acid synergistic urea intercalation exfoliation type MMT prepared in Example 2 was selected for comparison with Ca-MMT, and the XRD performance test results are shown in the figure. It can be seen that compared with the interlayer spacing of Ca-MMT of 1.25nm, the interlayer spacing of the intercalation type MMT prepared by the present invention has been expanded to 2.83nm, and the exfoliated MMT has no diffraction peak. Figure 2 and Figure 3 As shown in the electron microscope image, the obtained sodium-montmorillonite and graphene have a good lamellar structure.
[0060] Example 6
[0061] The exfoliated nano sodium montmorillonite prepared in Example 1 and PVA were used to prepare a PVA / phytic acid synergistic urea intercalation MMT composite material by using a tape casting method. 1g of phytic acid synergistic urea self-generated carbon dioxide to expand the interlayer spacing of the two-dimensional sheet material, 20g of polyvinyl alcohol, and 200g of deionized water were weighed, added to a three-necked flask and a condensing device was set up, heated to 100°C, maintained for 2h, and after the reaction was completed, the solution was sealed and allowed to stand at room temperature for 24h, and then cast into a film to obtain a PVA / phytic acid synergistic urea intercalation MMT composite material.
[0062] Comparative Example
[0063] The steps of this comparative example are the same as those of Example 6, except that in this comparative example, 0.5 g of montmorillonite, 0.01 mol of phytic acid, 0.06 mol of urea, 20 g of polyvinyl alcohol, and 200 g of deionized water were weighed and added into a three-necked flask, and montmorillonite / phytic acid / urea / PVA composite material was prepared by tape casting.
[0064] 1. Mechanical properties testing
[0065] Pure PVA was used as the control group, the PVA / phytic acid synergistic urea intercalated MMT composite material prepared in Example 6 and the montmorillonite / phytic acid / urea / PVA composite material prepared in the comparative example were selected for comparison, and the performance test results are shown in Table 1 below:
[0066] Table 1
[0067]
[0068] As can be seen from Table 1, the PVA composite material prepared by using phytic acid in conjunction with urea intercalated MMT in the present invention will reduce the tensile strength and Young's modulus of the PVA material, but greatly improve the elongation at break.
[0069] 2. Flame retardant performance test
[0070] The phytic acid prepared in Examples 1 to 5 cooperates with urea to self-generate carbon dioxide to expand the interlayer spacing of the two-dimensional sheet material and is compounded with PVA, and a phytic acid cooperates with urea to self-generate carbon dioxide to expand the interlayer spacing of the two-dimensional sheet material / PVA composite film is prepared by tape casting, and PVA to which phytic acid is not used to cooperate with urea to self-generate carbon dioxide to expand the interlayer spacing of the two-dimensional sheet material is used as a control group and a montmorillonite / phytic acid / urea / PVA composite material prepared in the comparative example is used as a comparison, and the flame retardancy of PVA is tested, and the test results are shown in Table 2 below:
[0071] Table 2
[0072] Flame retardant grade Example 1 VTM-0 Example 2 VTM-0 Example 3 VTM-0 Example 4 VTM-0 Example 5 VTM-0 Comparative Example VTM-1 Control group NR
[0073] As can be seen from Table 2 above, the present invention compounds phytic acid and urea, utilizes the phosphorus-nitrogen synergistic mechanism, and uses two-dimensional material sheets to fix carbon dioxide when carbon dioxide is generated between layers. The carbon dioxide between montmorillonite layers can be used to reduce the concentration of oxygen during the combustion process, thereby improving the flame retardancy of the material.
[0074] Obviously, the above embodiments of the present invention are merely examples for clearly illustrating the present invention, and are not intended to limit the embodiments of the present invention. For those skilled in the art, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the embodiments here. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present invention should be included in the protection scope of the claims of the present invention.
Claims
1. A method for preparing a two-dimensional sheet material by using phytic acid to cooperate with urea to self-generate carbon dioxide to expand the interlayer spacing, characterized in that: The preparation steps include: S1. dispersing the two-dimensional sheet material in deionized water to obtain a two-dimensional sheet material dispersion; S2. adding phytic acid and urea to the dispersion of the two-dimensional sheet material, and inserting the phytic acid and urea into the interlamellar space of the two-dimensional sheet material through cation exchange or thermal motion of molecules; S3. heating the solution of the intercalated two-dimensional sheet material so that the phytic acid between the layers reacts with urea to generate carbon dioxide; S4. After the interlayer reaction of phytic acid and urea, an exfoliated nano two-dimensional sheet material is obtained.
2. The method for preparing a two-dimensional sheet material by using phytic acid to cooperate with urea to self-generate carbon dioxide to expand the interlayer spacing according to claim 1, characterized in that: The two-dimensional sheet material includes sodium montmorillonite, calcium montmorillonite, black phosphorus, Ti4N3-MXene, Ti3C2T X -MXene, Ti2C-MXene, Nb2C-MXene, multilayer graphene, mica, diatomaceous earth, hexagonal boron nitride, molybdenum disulfide, mica, diatomaceous earth, hexagonal boron nitride, molybdenum disulfide or more.
3. The method for preparing a two-dimensional sheet material by using phytic acid to cooperate with urea to self-generate carbon dioxide to expand the interlayer distance according to claim 1, characterized in that: The dispersion described in S1 is carried out by ultrasonic dispersion, the ultrasonic time is 24 to 60 hours, and the ultrasonic frequency is 20 to 45 Hz.
4. The method for preparing a two-dimensional sheet material by using phytic acid to cooperate with urea to self-generate carbon dioxide to expand the interlayer spacing according to claim 1, characterized in that: The mass ratio of the two-dimensional sheet material to deionized water is 1:100-200.
5. The method for preparing a two-dimensional sheet material by using phytic acid to cooperate with urea to self-generate carbon dioxide to expand the interlayer spacing according to claim 1, characterized in that: The temperature of the cation exchange or the thermal motion of the molecules in S2 is 40 to 60°C, and the reaction time is 2 to 6 hours.
6. The method for preparing a two-dimensional sheet material by using phytic acid to cooperate with urea to self-generate carbon dioxide to expand the interlayer distance according to claim 1, characterized in that: The molar ratio of the phytic acid to the urea is 1:5-12.
7. The method for preparing a two-dimensional sheet material by using phytic acid to cooperate with urea to self-generate carbon dioxide to expand the interlayer distance according to claim 1, characterized in that: The mass ratio of the total mass of the phytic acid and the urea to the mass of the two-dimensional sheet material is 12 to 28:
1.
8. The method for preparing a two-dimensional sheet material by using phytic acid to cooperate with urea to self-generate carbon dioxide to expand the interlayer distance according to claim 1, characterized in that: The reaction temperature in S3 is 80-100°C, and the reaction time is 2-7h.
9. The method for preparing a two-dimensional sheet material by using phytic acid to cooperate with urea to self-generate carbon dioxide to expand the interlayer distance according to claim 1, characterized in that: The drying temperature of the exfoliated nano two-dimensional sheet material in S4 is 40 to 65 degrees Celsius, and the reaction time is 6 to 10 hours.
10. The method for preparing a two-dimensional sheet material by using phytic acid to cooperate with urea to self-generate carbon dioxide to expand the interlayer distance according to claim 1, characterized in that: The prepared peeled nano two-dimensional sheet material is used in flame-retardant polyamide, polyurethane, polyvinyl alcohol, polyimide, rubber and other materials.
Citation Information
Patent Citations
A kind of preparation method of organic acid salt intercalation modified montmorillonite
CN105733316B
Preparation method of phytic acid modified magnesium-aluminum hydrotalcite / montmorillonite nano material
CN114621771A
Cited By
Various polyvinyl alcohol-based nanocomposite composition with improved mechanical properties, water resistance, and flame retardancy and method of preparing the same
KR102980805B1